Challenges in modelling the Charcot-Marie-Tooth neuropathies for therapy development. Issue 1 (17th July 2018) - Juneja, Manisha; Burns, Joshua; Saporta, Mario A; Timmerman, Vincent
Abstract : Much has been achieved in terms of understanding the complex clinical and genetic heterogeneity of Charcot-Marie-Tooth neuropathy (CMT). Since the identification of mutations in the first CMT associated gene, PMP22, the technological advancement in molecular genetics and gene technology has allowed scientists to generate diverse animal models expressing monogenetic mutations that closely resemble the CMT phenotype. Additionally, one can now culture patient-derived neurons in a dish using cellular reprogramming and differentiation techniques. Nevertheless, despite the fact that finding a disease-causing mutation offers a precise diagnosis, there is no cure for CMT at present. This review will shed light on the exciting advancement in CMT disease modelling, the breakthroughs, pitfalls, current challenges for scientists and key considerations to move the field forward towards successful therapies.